2016
DOI: 10.3389/fpls.2016.01452
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Class of Plant Type III Polyketide Synthase Involved in Orsellinic Acid Biosynthesis from Rhododendron dauricum

Abstract: Rhododendron dauricum L. produces daurichromenic acid, the anti-HIV meroterpenoid consisting of sesquiterpene and orsellinic acid (OSA) moieties. To characterize the enzyme responsible for OSA biosynthesis, a cDNA encoding a novel polyketide synthase (PKS), orcinol synthase (ORS), was cloned from young leaves of R. dauricum. The primary structure of ORS shared relatively low identities to those of PKSs from other plants, and the active site of ORS had a unique amino acid composition. The bacterially expressed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 61 publications
0
38
0
Order By: Relevance
“…We have observed that, among the transcripts showing strong differential expression in the C. plicata clubs tissue, there is a putative PKS gene. Plant PKSs are known to catalyze the formation of a plethora of natural products, including plant volatiles [63], and recent studies have now shown that acetophenones, such as phloroacetophenone (2,4,6-trihydroxyacetophenone), are novel catalytic products of plant PKS [64] (Table 1). Alternatively, biosynthesis of acetophenones may involve coenzyme A (CoA)-dependent b-oxidation of phenylpropanoid pathway precursors, as has been highlighted in plants such as tobacco [65] and white spruce [66].…”
Section: Biosynthesis Of 2-hydroxy-6-methylacetophenonementioning
confidence: 99%
“…We have observed that, among the transcripts showing strong differential expression in the C. plicata clubs tissue, there is a putative PKS gene. Plant PKSs are known to catalyze the formation of a plethora of natural products, including plant volatiles [63], and recent studies have now shown that acetophenones, such as phloroacetophenone (2,4,6-trihydroxyacetophenone), are novel catalytic products of plant PKS [64] (Table 1). Alternatively, biosynthesis of acetophenones may involve coenzyme A (CoA)-dependent b-oxidation of phenylpropanoid pathway precursors, as has been highlighted in plants such as tobacco [65] and white spruce [66].…”
Section: Biosynthesis Of 2-hydroxy-6-methylacetophenonementioning
confidence: 99%
“…The FPKM value for RdFADOX1 was 74.7, which was much higher than those calculated for RdFADOX2 and RdFADOX3 (11.2 and 29.6,respectively). Notably, the gene for orcinol synthase (Taura et al, 2016; GenBank accession no. LC133082), the polyketide synthase involved in orsellinic acid biosynthesis in the DCA pathway, also is a highly expressed gene with an FPKM value of 81.9.…”
Section: Molecular Cloning and Sequence Analysis Of Dca Synthase Candmentioning
confidence: 99%
“…The gene-specific oligonucleotide primers and PCR conditions listed in Supplemental Table S3 were used for amplification of the RdFADOX1 to RdFADOX3 gene fragments. To obtain complete cDNA sequences, including untranslated regions, 3ʹ-and 5ʹ-RACE reactions were conducted as described previously (Taura et al, 2016). The cDNA template was prepared by RT of young leaf RNA using ReverTra Ace (Toyobo) and dT 17 AP primer.…”
Section: Cdna Cloning Of Rdfadox1 To Rdfadox3mentioning
confidence: 99%
See 1 more Smart Citation
“…are produced by type III PKS 3 -superfamily enzymes by iterative condensations of starter and extender acyl-CoA thioesters. Thus, in contrast to bacterial modular type I and dissociated type II PKS megaenzyme systems with multiple catalytic domains, such as ketoacyl synthase, acyltransferase, and acyl carrier protein (1,2), the structurally simple type III PKSs are homodimeric proteins of ϳ40-kDa subunits, which play a pivotal role in the remarkable structural diversification of polyketide backbone assemblies (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Each independent ketoacyl synthase domain in the type III PKS commonly maintains a "Cys-His-Asn" catalytic triad to catalyze the tethering of a CoA-linked starter substrate to the active-site Cys, which is followed by carbon-carbon (C-C) bond formation via decarboxylative Claisen-type condensation with an extender substrate (normally malonyl-CoA).…”
mentioning
confidence: 99%